Roadmap for Information Technology Artifacts Research with the Approach of Design Science - Fateme Aghapour; Shaban Elahi; Alireza Hassanzadeh; nasser Shahsavari-pour (Iranian Journal of Information Processing & Management)
The research method provides a way to solve or a systematic answer to the research problem. It is a framework forThe research method provides a way to solve to a research problem or a systematic answer to it. It is a framework for collecting, organizing, analyzing and presenting data to study the research problem. Design science research has emerged as an important approach in information systems research. Thus, this study is a systematic review of theoretical literature with a narrative analysis approach to create a comprehensive understanding of key concepts and specialized attitudes around design science research methods. A road map is designed to express how to use DSR to find the answer to the research question(s) about the design of information technology artifacts. The research is conducted with a systematic review method in two main steps. In the first step, the search for reliable sources was carried out using automatic approaches and snowball forward and backward in reliable databases. After the qualitative evaluation of the obtained sources, 52 articles were approved and selected based on specific criteria. In the second step and during the study, based on the narrative analysis method, four narratives emerged: the philosophical foundations of design science research, the theoretical development approach of research in design science, the methodological choice of design science research, and the strategy of design science research. Finally, using the narratives and concepts identified in each narrative, a mapping of the concepts and topics related to the four emerged theme of design science research was done and summarized and drawn in the form of a road map. The compiled roadmap presents the process of using the design science research method in the information technology artifacts design in a structured and accurate way for conducting design science research.